Relevance Of Cost Information, Transparency, Cost Distribution Towards Hospital Performance With Technology Development as a Moderation in Tangerang Regency - Hurian Kamela (Journal of Research in Social Science and Humanities, 2026)
This study aims to examine the effect of cost information relevance, transparency, and cost distribution on hospital performance, with technological development as a moderating variable in Tangerang Regency. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 148 respondents from the local community of Tangerang Regency as users of hospital services. The data analysis techniques include multiple linear regression and Moderated Regression Analysis (MRA) to test the moderating effect of technological development. The results reveal that cost information relevance, transparency, and cost distribution have a positive and significant impact on hospital performance. Furthermore, technological development is found to strengthen the relationship between cost information relevance, transparency, and cost distribution and hospital performance. These findings indicate that public perceptions of cost transparency, fair cost distribution, and the use of information technology play a crucial role in shaping hospital performance. This study provides practical implications for hospital management and local governments in improving cost management, service transparency, and information technology utilization to enhance hospital performance and public satisfaction sustainably.